2006
DOI: 10.3892/or.15.5.1273
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of low-dose 10-hydroxycamptothecin in human colon cancer

Abstract: Abstract. 10-Hydroxycamptothecin (10-HCPT), an indole alkaloid isolated from a Chinese tree, Camptotheca acuminate, inhibits the activity of topoisomerase I and has a broad spectrum of anticancer activity in vitro and in vivo. However, its use has been limited due to its water-insolubility and toxicity with i.v. administration. The purpose of this study was to investigate the efficacy, toxicity and proper dosage of 10-HCPT as a single agent by oral administration in the treatment of human colon cancer. 10-HCPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Flow cytometric analysis revealed that the number of apoptotic cells increased from 20.89% (following treatment with 2.5 nM HCPT) to 97.66% (following treatment with 20 nM HCPT) in a dose-dependent manner. So consistent with earlier observations in other tumor cells [19][20][21][22][23][24], we found that HCPT inhibits the proliferation and viability of SMS-KCNR cells by inducing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Flow cytometric analysis revealed that the number of apoptotic cells increased from 20.89% (following treatment with 2.5 nM HCPT) to 97.66% (following treatment with 20 nM HCPT) in a dose-dependent manner. So consistent with earlier observations in other tumor cells [19][20][21][22][23][24], we found that HCPT inhibits the proliferation and viability of SMS-KCNR cells by inducing apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Induction of apoptosis in tumor cells is a promising chemopreventive or chemotherapeutic strategy [17,18]. Previous studies have demonstrated that HCPT is able to induce apoptosis in cells of various tumor types, including colon, liver, gastric, prostate and bladder cancer, as well as melanoma [19][20][21][22][23][24]. However, only one study regarding HCPT-induced apoptosis of NB cells has been conducted [25].…”
Section: Discussionmentioning
confidence: 99%
“…The detached and attached cells were harvested and fixed in 70 % ice-cold methanol at -20°C overnight. After fixation, cells were washed with PBS, resuspended in 1 ml PBS containing 1 mg/ml RNase (Sigma, St. Louis, MO, USA), and 50 lg/ml propidium iodide (Sigma, St. Louis, MO, USA), and incubated at 37°C for 30 min in the dark (Ping et al 2006). Samples of 10,000 cells were then analyzed for DNA content and cell cycle phase distributions by using FACS-Calibur and Cell-Quest software (Becton-Dickinson Biosciences).…”
Section: Analyses Of Cell Viabilitymentioning
confidence: 99%
“…10-HCTN significantly repressed the proliferation of colon 205 cells at a relatively low concentration (5 -20 nM). HCPT-induced ultra-structural changes in nuclei and nuclear matrix were similar to those typically associated with lesions of DNA replication or RNA transcription [1][2][3][4]. 10-HCTN is obtained by a total synthesis involving 13 steps.…”
Section: Introductionmentioning
confidence: 99%